The Novel Regulatory Role of the lncRNA–miRNA–mRNA Axis in Chronic Inflammatory Airway Diseases - Qiao, Xin; Hou, Gang; He, Yu-Lin; Song, Dong-Fang; An, Yi; Altawil, Abdullah; Zhou, Xiao-Ming; Wang, Qiu-Yue; Kang, Jian; Yin, Yan (Frontiers in Molecular Biosciences, 2022)
Chronic inflammatory airway diseases, characterized by airway inflammation and airway remodelling, are increasing as a cause of morbidity and mortality for all age groups and races across the world. The underlying molecular mechanisms involved in chronic inflammatory airway diseases have not been fully explored. MicroRNAs (miRNAs) and long noncoding RNAs (lncRNAs) have recently attracted much attention for their roles in the regulation of a variety of biological processes. A number of studies have confirmed that both lncRNAs and miRNAs can regulate the initiation and progression of chronic airway diseases by targeting mRNAs and regulating different cellular processes, such as proliferation, apoptosis, inflammation, migration and epithelial–mesenchymal transition (EMT). Recently, accumulative evidence has shown that the novel regulatory mechanism underlying the interaction among lncRNAs, miRNAs and messenger RNAs (mRNAs) plays a critical role in the pathophysiological processes of chronic inflammatory airway diseases. In this review, we comprehensively summarized the regulatory roles of the lncRNA–miRNA–mRNA network in different cell types and their potential roles as biomarkers, indicators of comorbidities or therapeutic targets for chronic inflammatory airway diseases, particularly chronic obstructive pulmonary disease (COPD) and asthma.